Bulgarian yesterday, today, tomorrow (to the publication of the book Slawistik. —Band 8: Sprachwissenschaftliche Perspektiven der Bulgaristik: Standpunkte — Innovationen — Herausforderungen der Bulgaristik: Festschrift für Prof. Dr. h. c. Helmut Wilhelm Schaller anlässlich seines 80. Geburtstags / M. Henzelmann (Hg.). — Berlin : Frank & Timme GmbH, 2020. — 342 S.) - S. G. Shulezhkova (Tsentr nauchnykh i obrazovatelnykh proektov, 2020)
Against the background of the achievements of Bulgarian studies at the end of the 20th and beginning of the 21st centuries, the author considers the problems discussed in the 8th volume of the book “Slawistik” (2020) entitled  “Linguistic Perspectives of Bulgaria: State — Innovation — Challenges”. Particular attention is paid to the areas of  scientific research of Bulgarians from around the world. The novelty of the research lies in the fact that the  thematic issue of the book is analyzed in connection with the processes that the modern Bulgarian language and the science about it are going through in the digital civilization. The analysis is projected on the achievements of Bulgarian linguistics, developing after the collapse of the USSR and the disappearance of the socialist camp in the broad context of the linguistic science of the European Union. The authors of the article proceed from the fact that the language of the people numbering about 9 million people cannot but experience the powerful influence of the  languages of international communication. The importance of turning Bulgarians to the common origins of Slavic culture, establishing scientific and cultural contacts to maintain the national identity of the languages of the Slavic peoples is emphasized in the article. The relevance of the results of the proposed analysis is due to the need for closer cooperation of Slavists, including Russia and Bulgaria, in order to comprehensively study and support the Bulgarian language.